Is Finnish äiti ‘mother’ a Gothic loanword? - Witczak, Krzysztof Tomasz; Wojan, Katarzyna (Papers in Linguistics, 2025)
Some time ago, linguists recognized that the Gothic term aiþei f. ‘mother’ has some Nordic and West Germanic equivalents but lacks cognates in other Indo-European languages. Its origins, as well as its etymology, semantic motivation and morphological structure remain unclear. On the other hand, in Western Finnic (Baltic Finnic) languages there is a phonologically similar term *äitei ‘mother’ (cf. Old Finnish äitei [1548], recorded by Mikael Agricola), attested in Finnish, Karelian, Estonian and Võro and their numerous dialects and jargons. There is no doubt that we are dealing here with an ancient borrowing resulting from prehistoric linguistic contacts between the Proto-Germanic and West Finnic populations. The existing literature on the subject unanimously points to the Germanic source of the borrowing. In the article, the authors argue for the Finnish origin of this kinship term. The correct direction of the borrowing (Gothic aiþei < PG. *aiþī ← BFi. *äitei) is motivated by both a convincing etymology (BFi. *äitei ‘mother’, also ‘old woman’ ← Uralic *äji ‘old, great’, *äjjä ‘old man, grandfather’) and a perfect morphological parallel (BFi. *neitei ‘maiden, girl’ < Finno-Ugric *nejδej ‘girl, maiden, daughter’ ← Uralic *näxi ‘young woman’).